Large amplitude spin-Hall oscillations due to field-like torque. (20th April 2021) - Arun, R; Gopal, R; Chandrasekar, V K; Lakshmanan, M
Abstract: Large amplitude spin-Hall oscillations are identified in a ferromagnetic layer with two perpendicular in-plane easy axis in the presence of field-like torque without any polarizer and external field. The analytical study confirms the possibility of oscillations in the presence of field-like torque. The investigation shows that the oscillation frequency can be tuned from ∼2 GHz to ∼80 GHz by current and enhanced by field-like torque. Further, the enhancement of frequency along with the Q -factor by current and field-like torque is also observed.